RNA directed DNA methylation and seed plant genome evolution - Wambui Mbichi, R.; Wang, Qing-Feng; Wan, Tao (Plant cell reports, 2020)
RNA Directed DNA Methylation (RdDM) is a pathway that mediates de novo DNA methylation, an evolutionary conserved chemical modification of cytosine bases, which exists in living organisms and utilizes small interfering RNA. Plants utilize DNA methylation for transposable element (TE) repression, regulation of gene expression and developmental regulation. TE activity strongly influences genome size and evolution, therefore making DNA methylation a key component in understanding divergence in genome evolution among seed plants. Multiple proteins that have extensively been studied in model plant Arabidopsis thaliana catalyze RNA dependent DNA Methylation pathway along with small interfering RNA. Several developmental functions have also been attributed to DNA methylation. This review will highlight aspects of RdDM pathway dynamics, evolution and functions in seed plants with focus on recent findings on conserved and non-conserved attributes between angiosperms and gymnosperms to potentially explain how methylation has impacted variations in evolutionary and developmental complexity among them and advance current understanding of this crucial epigenetic pathway.